The Role of School Psychologists in the Implementation of Trauma-Informed Multi-Tiered Systems of Support in Schools. Issue 4 (12th November 2020) - Ormiston, Heather E.; Nygaard, Malena A.; Heck, Olivia C.
Abstract: The National Child Traumatic Stress Network has applied a trauma-informed (TI) lens to a multi-tiered systems of support framework, referred to as TI-MTSS. The NCTSN presents 10 Core Area guidelines to guide school personnel toward the implementation of TI-MTSS. The purpose of this paper is to connect the training and expertise of school psychologists to a rationale that school psychologists are ideally positioned to lead the efforts of TI-MTSS in schools. Framed in the 10 Core Area guidelines provided by the National Child Ttraumatic Stress Network, we operationalize the school psychologist's role and skills within each of the 10 Core Area domains.